Soluble Fas Ligand as a Potential Marker of Severity of Dengue Infection - Dr. dr. Nurfadly, MKT. (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
Background, The apoptosis of microvascular endothelial cells causes plasma leakage in dengue haemorrhagic fever patients. The soluble Fas ligand is a p1'0tein with molecular weight of 40 kDa that acts as a mediator of apoptosis. This study aimed to prove whethe1· soluble Fas ligand can be used as a pote8 marker to predict the severity of dengue infection by comparing the soluble Fas ligand levels jn denb'Ue fever (DF) and dengue haemorrhagic fever (DHF) patients early in the course ofi illness. Method: This was a prospective study. It included 42 de01e patients (22 DF patients and 20 DHF atients) and 20 healthy le as a control group. The